If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -1(3h + 2) = 1 + -1(5 + -7h) Reorder the terms: 4 + -1(2 + 3h) = 1 + -1(5 + -7h) 4 + (2 * -1 + 3h * -1) = 1 + -1(5 + -7h) 4 + (-2 + -3h) = 1 + -1(5 + -7h) Combine like terms: 4 + -2 = 2 2 + -3h = 1 + -1(5 + -7h) 2 + -3h = 1 + (5 * -1 + -7h * -1) 2 + -3h = 1 + (-5 + 7h) Combine like terms: 1 + -5 = -4 2 + -3h = -4 + 7h Solving 2 + -3h = -4 + 7h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-7h' to each side of the equation. 2 + -3h + -7h = -4 + 7h + -7h Combine like terms: -3h + -7h = -10h 2 + -10h = -4 + 7h + -7h Combine like terms: 7h + -7h = 0 2 + -10h = -4 + 0 2 + -10h = -4 Add '-2' to each side of the equation. 2 + -2 + -10h = -4 + -2 Combine like terms: 2 + -2 = 0 0 + -10h = -4 + -2 -10h = -4 + -2 Combine like terms: -4 + -2 = -6 -10h = -6 Divide each side by '-10'. h = 0.6 Simplifying h = 0.6
| (15*2)+(w*2)=50 | | 20a^2+16a^3= | | .20x=30 | | 2v-8=3v+5 | | 4(2x+4)=10x+15+1 | | 9y^2-13y^3= | | -5x+y=15 | | 40.00(1.50)=1.55+40 | | -15+x=37 | | -7x-7=35 | | 9b+6b^3= | | 4x+2y=210 | | 25x^2-2x+4=0 | | 19.99+0.35x=29.99 | | 8y=2+5 | | 5(k+2)=5(k+4) | | 50=2x-5 | | 4c^2=36c | | 3(4g+1)-g=8-1(3g+2) | | -23d+25d+86=-60 | | 5cos(5x)=0 | | -8=-4+d | | 7(y-9)=21 | | 15x-15x+9x-7x-x+5=26 | | 4z+10=z-2+3 | | 5=7(q-5)-19 | | -5x-8=13+8(x+3) | | 7x+8+8x+3=17x-19 | | 3.8-(7.45)= | | 67m-27m-18m-21m+8=81 | | 10x+15y=200 | | 0=(-5/7)x+4 |